[OP.1A.03] COPEPTIN LEVELS IN PATIENTS WITH TREATMENT RESISTANT HYPERTENSION BEFORE AND AFTER RENAL DENERVATION. (September 2017) - Jumar, A.; Ott, C.; Schmid, A.; Kannenkeril, D.; Ditting, T.; Veelken, R.; Uder, M.; Schmieder, R.E.
Abstract : Objective: Copeptin, the C-terminal peptide of pro-vasopressin which is released from the neurohypophysis, reflects the activity of the hormone arginine vasopressin. Copeptin has been found to be associated with cardiovascular and all-cause mortality in patients with hypertension. The aim of this study is to compare copeptin levels in patients with treatment resistant hypertension (TRH) before and 6 months after renal denervation. Design and method: Copeptin was measured in 43 patients with TRH and in 30 patients with primary hypertension stage 1 or 2 (HT) using ELISA Elabscience®. In addition, copeptin levels were measured in patients with TRH at 6 month follow-up visit after renal denervation. Renal denervation was performed by an experienced person applying at least four ablations longitudinally and rotationally within the lengths of each renal artery to cover a full four quadrant ablation. Results: Patients with TRH showed systolic and diastolic ambulatory BP of 154 ± 14/ 87 ± 12 mmHg before and systolic and diastolic ambulatory BP of 144 ± 13/ 82 ± 8 mmHg after renal denervation (p < 0.001). There was no significant difference in copeptin levels in 43 patients (age 61 years) before and six months after renal denervation (10.9 ± 10.8 vs 12.5 ± 14.6 pmol/l, p = 0.287). Patients with TRH showed higher copeptin levels compared to patients with HT (age 47 years, systolic and diastolic ambulatory BP (142  ± 11/ 90 ± 8 mmHg) (copeptin conc.: 5.8 ± 4.8 vs 10.9 ± 10.8 pmol/l, p = 0.007). In patients with HT there was a correlation between copeptin concentrations and diastolic 24 h ambulatory BP (r = 0.428, p = 0.018). Conclusions: Patients with TRH showed nearly 2 fold higher copeptin levels than patients with HT. Renal denervation did not lead to any change of copeptin levels in patients with TRH six month after procedure.